2000
DOI: 10.1103/physrevb.62.5117
|View full text |Cite
|
Sign up to set email alerts
|

Growth and lattice dynamics of Co nanoparticles embedded in Ag: A combined molecular-dynamics simulation and Mössbauer study

Abstract: We use Mössbauer spectroscopy in combination with atomic scale modeling in order to gather a comprehensive understanding of the growth and the dynamics of cobalt nanoprecipitates in silver. The modeling makes use of classical molecular dynamics in the canonical ensemble by means of the Rahman-Parinello technique. Atomic interactions are governed by an embedded atom model, which is validated for the static Co-Ag interaction by means of a comparison with extended x-ray absorption fine structure measurements and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
46
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 32 publications
8
46
0
Order By: Relevance
“…From Fig. 3, it can be seen that the size effects on Q D (x, r, d) of Zr 90 Al 10 and Zr 84 Al 16 nanoparticles are different. This is ascribed to the strong composition effect in bimetallic nanocrystals, in particular for the mixture of alloy components with distinct lattice constants.…”
mentioning
confidence: 92%
“…From Fig. 3, it can be seen that the size effects on Q D (x, r, d) of Zr 90 Al 10 and Zr 84 Al 16 nanoparticles are different. This is ascribed to the strong composition effect in bimetallic nanocrystals, in particular for the mixture of alloy components with distinct lattice constants.…”
mentioning
confidence: 92%
“…It is interesting to note that the surface mode contribution of nanoclusters can largely influence the MSRD. Also, Hou and co-workers 10 revealed that the strong relaxation takes place at the Co cluster-Ag matrix interface due to cluster size dependent atomic arrangements. The atomic vibrational properties at the interface depend functionally on cluster size and a discontinuity of the amplitudes at the Co/Ag interface.…”
Section: Introductionmentioning
confidence: 99%
“…However, little has been known insofar from the perspective of the atomistic origin about the quantitative MSRD in nanosolids under the conditions of coupling effects of high pressure and high temperature. 10,13 In this paper, we developed a solid size, pressure, and temperature dependence of Debye temperature to elucidate the total MSRD of a nanosolid. Importantly, the theoretical predictions made on the basis of the proposed model are in agreement with the experimental measurements and simulations results.…”
Section: Introductionmentioning
confidence: 99%
“…(13) with d = 0, 1 and 2 for the nanoparticles, the nanowires or nanorods and the thin films, respectively, while the computer simulation results are done with d = 0 [117,122]. The ∞ ∞ ∞ granular films cannot be described as a continuous film [108,118] since they are of high densities of inner surfaces or grain boundaries.…”
Section: The Verification Of the Modelmentioning
confidence: 99%